Towards a governance of sustainability transitions: Giving place to individuals - Felix Rauschmayer; Tom Bauler; Niko Schäpke (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
Policies for sustainability transitions necessarily have three main characteristics: they are prescriptive with regard to dynamic societal processes, linked to the normativity of sustainable development, and are able to interlink both the societal and the individual levels. Taking transition management as a starting point, the paper elaborates that it cannot well address the second and third characteristic. We therefore suggest complementing transition management approaches with the individualistic capability approach and the more structural practice theory. We suggest a heuristic combination that places individuals back into the study of sustainability transitions and show with three suggestions how this might change research on and for transitions. Firstly, we propose to assess sustainability on individual, niche, and regime level; Secondly, we show that the crucial learning processes occurring in the transition processes can be better understood when interrelating the three levels; Finally, we elaborate that the governance of sustainability transitions necessarily has - at the same time - to foster free spaces for experimentation and to select those niches that are conducive to more instead of less sustainability.
Keywords: 330